2021
DOI: 10.3389/fpsyg.2021.702678
|View full text |Cite
|
Sign up to set email alerts
|

Elevating Subjective Well-Being Through Physical Exercises: An Intervention Study

Abstract: Background: Physical activity is associated with higher levels of subjective well-being. However, little research has been conducted in naturalistic conditions with a longitudinal design. In the current study, we aimed to examine whether regular activity initiation can impact happiness, life satisfaction, and self-esteem 4 weeks later.Methods: The sample (N = 217, 124 women) was divided into three groups based on level of physical activity (active people, beginners, and inactive people). The participants compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 97 publications
1
16
0
Order By: Relevance
“…Diener noted that the subjective well-being consists of three dimensions, life satisfaction, positive affect, and negative affect, and pointed out that subjective well-being is positively correlated with life satisfaction and positive affect, and negatively correlated with negative affect [ 23 ]. People who engage in long-term activities are more optimistic than those who exercise less, and they have a greater life satisfaction and happiness [ 24 , 25 ]. Li and Liu pointed out that exercise can directly increase individuals’ well-being, and the more exercise people do, the stronger their perception of well-being, and the better their life satisfaction [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diener noted that the subjective well-being consists of three dimensions, life satisfaction, positive affect, and negative affect, and pointed out that subjective well-being is positively correlated with life satisfaction and positive affect, and negatively correlated with negative affect [ 23 ]. People who engage in long-term activities are more optimistic than those who exercise less, and they have a greater life satisfaction and happiness [ 24 , 25 ]. Li and Liu pointed out that exercise can directly increase individuals’ well-being, and the more exercise people do, the stronger their perception of well-being, and the better their life satisfaction [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been described that physical activity influences well-being and personal realization, as well as pain avoidance [ 63 ]. This association could be explained by the fact that military personnel with a high level of physical activity probably generate significantly higher levels of life satisfaction, self-esteem, and happiness compared to inactive people, especially because the biological pathways of physical activity act as a buffer against stress and stress-related disorders, optimize neuroendocrine and physiological responses to stressors and promote an anti-inflammatory system, improving neuroplasticity along with growth factor expression [ 64 ], and even generate lower levels of anxiety; thus improving their self-efficacy and motivation during daily life [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the intrinsic physiological mechanism of subjective well-being as a mediating variable, the Dsouza study concluded that people who exercise regularly have higher levels of happiness, possibly due to higher levels of endorphins in their bodies, which trigger positive emotions. 69 Also, a study by Iwon suggests that regular PA is associated with higher levels of subjective well-being, possibly due to PA promoting the release of dopamine, 70 which alleviates negative emotions such as depression and anxiety. PA is of great importance to college students.…”
Section: Discussionmentioning
confidence: 99%